[Mummery, Browning (singer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Joseph Browning Mummery (12 July 1888 - 16 March 1974), was an Australian opera tenor of the 1920s and '30s who achieved a considerable reputation in Europe as well as Australia. Mummery was born in Carlton, Melbourne, and initially studded under the Italian baritone A. C. Bartleman. He began his operatic career in 1920, with the Gonzales Opera Company. He sang with Dame Nellie Melba in La Bohème and worked with conductors such as Sir John Barbirolli, Sir Malcolm Sargent, Sir Thomas Beecham and Sir Henry Wood. He sang extensively in America and later taught in Melbourne, and appeared as the solo tenor in the 1934 film, Evensong with Evelyn Laye. He retired to Canberra, where he died on 1974, aged 85.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
For information about other performances by this artist, see also the 'Symphony Australia collection of concert touring schedules and artist itineraries 1934 to 1997' in the Library's catalogue.
Keywords: Mummery, Browning, -- 1888-1974 -- Miscellanea; Tenors (Singers) -- Australia -- Miscellanea; Singers -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian